STUDY ON MEDICINAL VALUE OF HERBS AND VEGETABLES COMMONLY USED IN MANIPURI CUISINE THROUGH AYURVEDIC PERSPECTIVE (AYUSHDHARA, 2017)
North east India is rich in medicinal plant diversity. Manipur, a state of north-eastern India, which falls in the Indo-burma border is known for its ecologically distinctive and rich biodiversity, having many endemic flora and fauna and rich cultural diversity. Herbs and spices form a very important part of Manipuri cuisine, specially for the Meitei community. The Meitei community typically raise vegetables in their kitchen garden therefore their cuisine is very much seasonal. In this article 14 herbs and vegetables are included for study. Some of the herbs are- Mayang-ton (lemon basil), Mukthrubi (Chamelon plant), Phakpai (Polygonum posumber) etc. Further many large varieties of vegetables that are used in daily meals are found in and around the region and not seen elsewhere. Some of them are Yongchak (tree bean), Sougri (Hibiscus Cannabinus), Yeli (water caltrop) etc. These herbs and vegetables are used in day to day life but people are mostly unaware of the various health benefit of them. Now it's high time to make the general masses aware about the benefits of their own traditional cuisine. Redefining them through Ayurvedic perspective will enable in knowing the medicinal action on Dosha and will help in promoting the knowledge to local people and physician to use these local herbs and vegetables appropriately and wisely on different disease treatment and prevention.